Characteristics of Microplastic in Commercial Aquatic Organisms - Risky Ayu Kristanti; Wei Lin Wong; Yeti Darmayati; Ariani Hatmanti; Nilam Fadmaulidha Wulandari; Mada Triandala Sibero; Nur Fitriah Afianti; Erika Hernandes; Flavio Lopez-Martinez (Tecno Scientifica Publishing, 2022)
This study aims to review the occurrence of microplastics in some commercial aquatic organisms. Microplastics are small plastic particles with a diameter of less than 5 mm. Effluent, stormwater, agricultural, and surface runoff introduce microplastic to freshwater basins. Hydrodynamics and hydrology encompass microplastics. River flow speed can cause turbulence and riverbed instability, increasing microplastic concentrations. Fish, shellfish, and crustaceans ingest microplastics in proportion to their quantity in freshwater and marine environments. Human activities cause variations in the form, color, and size of microplastics in the biota. Animals absorb microplastics through trophic transfer. Increased microplastic residence time before ingestion promotes trophic transmission. Lower food concentration and aggregation enhance microplastic retention in zooplankton guts, increasing transmission to higher-trophic-level species. Most studies show that microplastics in biota are discovered in fish and crustacean intestines and bivalve tissues. Microplastic buildup can disrupt live organisms' growth and reproduction, induce oxidative stress, obstruct the digestive system, and damage the intestine. Microplastics may harm people's health if they eat contaminated seafood that contains them, but more research is needed.